The efficacy of personalized psychological interventions in adolescents: a scoping review and meta-analysis - Li, William; Gleeson, John; Fraser, Madeleine I.; Ciarrochi, Joseph; Hofmann, Stefan G.; Hayes, Steven C.; Sahdra, Baljinder (Frontiers in Psychology, 2024)
This review compared the efficacy of personalized psychological interventions to standardized interventions for adolescents. We conducted a scoping review and meta-analysis of randomized controlled trials that compared personalized interventions with standardized interventions in adolescents. Data was analyzed using Bayesian multilevel random effects meta-analysis. Eligible studies were identified through five databases: Scopus, PsycINFO, MEDLINE, Web of Science, and EMBASE. Moderation analysis was conducted to explain potential sources of effect size heterogeneity. Eight studies across 13 articles (participant N = 2,490) met inclusion criteria for the review with seven studies across 10 articles (N = 1,347) providing sufficient data for inclusion in the meta-analysis. A small but significant effect size favoring personalized interventions was found (d = 0.21, 95%CrI [0.02, 0.39]), indicating that personalized interventions are associated with superior treatment outcomes compared to standardized interventions.Moderate between-study heterogeneity was found (I 2 = 53.3%). There was no evidence of publication bias. The review also found significant variation in methods of treatment personalization. This review provides evidence that personalization of adolescent psychological interventions is an effective way to improve treatment outcomes. Given the large number of adolescents worldwide who will experience some sort of mental health problem, personalization could have a significantly large impact on global mental health outcomes.